PRECOCITY, YIELD AND POSTHARVEST PHYSICAL AND CHEMICAL PROPERTIES OF PLUMS RESISTANT TO SHARKA GROWN IN SERBIAN CONDITIONS - Nebojša Milošević; Evica Mratinić; Ivana S. Glišić; Tomo Milošević (Acta Scientiarum Polonorum: Hortorum Cultus, 2012)
The study focused on characterizing the three German plum cultivars (‘Jojo’, ‘Hanita’ and ‘Katinka’) hypersensitive (oversensitiveness) and/or tolerant to Sharka to acknowledge the tree vigour, precocity, yield performances and main physico-chemical quality attributes of the fruits grown in a Serbian agro-climatic conditions. The cultivars were grafted on ‘Wangenheim Prune’ seedlings rootstock and established at a 4 × 1.5 m. The following determinations were assessed: trunk cross sectional area, yield per tree and unit area, yield efficiency, fruit and stone mass, fruit linear dimensions, flesh rate, geometric mean diameter, sphericity, aspect ratio, surface area, soluble solids and sugars content, titratable acidity, and ratio between them, respectively. The cultivar per se (genotype) behaved as the most influencing factor conditioning plum tree vigour, yield characteristics, physical attributes, soluble solids content, titratable acidity and sugar profiles. The assessment of plum chemical compositions implies the great potential of German cultivars for fresh market, fruit processing and drying. In fact, the ‘Katinka’ seems particularly suitable for fresh consumption, whereas ‘Jojo’ and ‘Hanita’ can be recommended for fresh consumption, processing and drying. Finally, all three cultivars grafted on ‘Wangenheim Prune’ seedlings can be recommended for growers in similar conditions.